Financial stability considerations for monetary policy: Empirical evidence and challenges - Nina Boyarchenko; Giovanni Favara; Moritz Schularick (Federal Reserve Bank of New York, 2022)
This paper reviews literature on the empirical relationship between vulnerabilities in the financial system and the macroeconomy, and how monetary policy affects that connection. Financial vulnerabilities build up over time, with both risk appetite and risk taking rising during economic expansions. To some extent, financial crises are predictable and have severe real economic consequences when they occur. Empirically it is difficult to link monetary policy to financial vulnerabilities, in part because financial cycles have long durations, making it difficult to separate effects of changes in monetary policy from other business cycle effects.
Keywords: E44; E52; E58; G2; 330; monetary policy; financial stability; financial crises; credit; leverage; liquidity; asset prices